2010
DOI: 10.1161/strokeaha.109.558809
|View full text |Cite
|
Sign up to set email alerts
|

Differing Risk Factor Profiles of Ischemic Stroke Subtypes

Abstract: Background and Purpose-Differences in risk factor profiles between lacunar and other ischemic stroke subtypes may provide evidence for a distinct lacunar arteriopathy, but existing studies have limitations. We overcame these by pooling individual data on 2875 patients with first-ever ischemic stroke from 5 collaborating prospective stroke registers that used similar, unbiased methods to define risk factors and classify stroke subtypes. Methods-We compared risk factors between lacunar and nonlacunar ischemic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
2
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 38 publications
(23 reference statements)
6
94
2
13
Order By: Relevance
“…Although treatment of hyperglycemia appears to more successfully reduce microvascular disease than disease due to large-artery atherosclerosis, 8 in a recent systematic review diabetes was equally associated with lacunar and nonlacunar ischemic stroke. 21 However, in all studies included in this review, lacunar infarction was defined clinically, requiring the presence of lacunar symptoms. Therefore, the lacunes studied tend to represent Fisher's microatheromatous lacunar subtype, which we believe is more similar than smaller lacunes to large-artery cerebral infarctions.…”
Section: Statistical Analysis Since Lipohyalinotic Lesions Are Assumedmentioning
confidence: 99%
“…Although treatment of hyperglycemia appears to more successfully reduce microvascular disease than disease due to large-artery atherosclerosis, 8 in a recent systematic review diabetes was equally associated with lacunar and nonlacunar ischemic stroke. 21 However, in all studies included in this review, lacunar infarction was defined clinically, requiring the presence of lacunar symptoms. Therefore, the lacunes studied tend to represent Fisher's microatheromatous lacunar subtype, which we believe is more similar than smaller lacunes to large-artery cerebral infarctions.…”
Section: Statistical Analysis Since Lipohyalinotic Lesions Are Assumedmentioning
confidence: 99%
“…Hypertension and diabetes appeared equally common in LS and NLS. Atrial fibrillation and carotid stenosis were associated more with NLS than LS (Jackson et al, 2010).…”
Section: Discussionmentioning
confidence: 87%
“…However, in lacunar stroke, hyperglycemia was not associated with functional outcome. Jackson et al (2010) systematically reviewed studies comparing risk factors in patients with lacunar stroke versus non-lacunar stroke. They reported that 16 of 28 studies included risk factors in their ischemic stroke subtype definitions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jackson et al 1,2 found that cardiovascular risk factors, such as hypertension and diabetes mellitus, are equally common in nonlacunar and lacunar infarcts, but atrial fibrillation or cardiac valve disease and significant carotid artery stenosis were more frequent in nonlacunar infarcts compared with lacunar infarcts, supporting the notion of separate etiologies. Others have found a lower risk of early stroke recurrence and myocardial infarction in patients with lacunar versus nonlacunar infarcts.…”
mentioning
confidence: 99%